The impact of national democratic representation on decision-making in the European Union. Issue 1 (2nd January 2022) - Kleine, Mareike; Arregui, Javier; Thomson, Robert
ABSTRACT: The extent to which decision-making in the European Union (EU) is responsive to national democratic representation has profound implications for understanding how the EU works in practice and for assessing it normatively. The contributions to this special issue examine key aspects of national representation, including national public opinion, elections and partisan government control. They do so with a shared theoretical approach and a newly updated common dataset, which facilitates cumulative knowledge. Here, we identify some of the main findings and their implications. Despite seismic political changes in many national arenas, EU decision-making is marked by more continuity than change. The evidence indicates that EU decision-making does respond to national democratic processes, but in ways that are highly conditional. For instance, member states' negotiating positions in the EU are shaped by public opinion and national parties' positions, but this responsiveness is conditioned by the presence of Euroscepticism, the timing and competitiveness of national elections and coalition politics. We discuss the contrasting implications of the findings from the perspectives of promissory representation and liberal democratic theory.